Multiple linear leiomyomas of the forehead as the presenting sign of Reed syndrome. (30th September 2013) - Kakar, Rohit; Davis, Jeremy C.; Crowe, David R.
Abstract A 62‐year‐old female presented with a linear arrangement of multiple asymptomatic, discrete, dome‐shaped, smooth, skin‐colored papules and nodules involving the left forehead. Histopathology showed a poorly circumscribed nodule of haphazardly arranged fascicles of smooth muscle cells involving the papillary and superficial reticular dermis. Genetic testing revealed the patient to be heterozygous for the R233H mutation in the fumarate hydratase gene. Clinical, microscopic, and genetic findings were consistent with a diagnosis of Reed syndrome. Reed syndrome is a rare disorder defined by cutaneous and uterine leiomyomas and, uncommonly, renal cell carcinoma.